Shipping noise - Kozaczka, E.; Grelowska, G. (Archives of Acoustics, 2004)
The aim of this paper is to present the result of the experimental research associated with the transmission of acoustic energy generated by a moving ship and its impact on the marine animals. The methodology of evaluation of the transmission of vibration energy from the ship’s mechanisms into the sea environment is given and some examples of underwater characteristics of ship’s noise are shown. All of these characteristics should reflect individual features of the source that is a moving ship or a warship. Knowledge of them gives information what steps should be undertaken to obtain specified characteristics of the source. Besides, the characteristics allow to assess, which factors are the most disadvantageous to the surrounding and whether their reduction is possible without changes of operational variables of the ship.